Minimizing inhibition of PCR-STR typing using digital agarose droplet microfluidics. (January 2015) - Geng, Tao; Mathies, Richard A.
Highlights: PCR inhibitory effects can be overcome by digital agarose droplet microfluidics technology. Single-cell STR typing is performed on samples contaminated with high concentrations of urea, tannic acid and humic acid. Extremely diluted DNA samples are typed in the presence of humic acid by single-molecule digital droplet PCR. Abstract: The presence of PCR inhibitors in forensic and other biological samples reduces the amplification efficiency, sometimes resulting in complete PCR failure. Here we demonstrate a high-performance digital agarose droplet microfluidics technique for single-cell and single-molecule forensic short tandem repeat (STR) typing of samples contaminated with high concentrations of PCR inhibitors. In our multifaceted strategy, the mitigation of inhibitory effects is achieved by the efficient removal of inhibitors from the porous agarose microgel droplets carrying the DNA template through washing and by the significant dilution of targets and remaining inhibitors to the stochastic limit within the ultralow nL volume droplet reactors. Compared to conventional tube-based bulk PCR, our technique shows enhanced (20×, 10×, and 16×) tolerance of urea, tannic acid, and humic acid, respectively, in STR typing of GM09948 human lymphoid cells. STR profiling of single cells is not affected by small soluble molecules like urea and tannic acid because of their effective elimination from the agarose droplets; however, higher molecular weight humic acid still partially inhibits single-cell PCR when the concentration is higher than 200 ng/μL. Nevertheless, the full STR profile of 9948 male genomic DNA contaminated with 500 ng/μL humic acid was generated by pooling and amplifying beads carrying single-molecule 9948 DNA PCR products in a single secondary reaction. This superior performance suggests that our digital agarose droplet microfluidics technology is a promising approach for analyzing low-abundance DNA targets in the presence of inhibitors.